FORENSIC ANALYSIS OF DIGITAL ARTIFACTS OF QR CODE PHISHING ATTACK AT 'AISYIYAH UNIVERSITY YOGYAKARTA - Yunan Al-husaini Djaibakal; Arizona Firdonsyah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2026)
Abstract: The use of QR Codes in academic settings has increased with the digitization of attendance systems, but it has also introduced potential abuse in the form of quishing attacks (QR phishing). Previous studies have mainly focused on user behavior, while forensic analysis of digital artifacts as evidence is still limited. This study aims to conduct a forensic analysis of browser artifacts resulting from interactions with dangerous QR Codes at Aisyiyah University Yogyakarta using the framework of the National Justice Institute (NIJ). Six investigation parameters are defined: domain identification, endpoint identification, identification of supporting resources, visualization of image artifacts, timestamp correlation, and HTML reconstruction. Data is obtained from the Google Chrome profile directory and analyzed using Autopsy, focusing on Web Cache, Browser History, and Cookies artifacts. The results showed that five parameters were successfully identified with an investigation success rate of 83.3%, while HTML reconstruction could not be fully achieved due to cache limitations. These findings show that Web Cache artifacts provide evidentiary value in the forensic investigation of QR Code-based attacks. Future research should focus on improving full-page reconstruction techniques. Keywords: browser forensics; digital artifacts; NIJ; quishing; Web Cache Abstrak: Penggunaan Kode QR di lingkungan akademik telah meningkat seiring dengan digitalisasi sistem absensi, tetapi juga menimbulkan potensi penyalahgunaan dalam bentuk serangan phishing (QR phishing). Studi sebelumnya sebagian besar berfokus pada perilaku pengguna, sementara analisis forensik artefak digital sebagai bukti masih terbatas. Studi ini bertujuan untuk melakukan analisis forensik artefak browser yang dihasilkan dari interaksi dengan Kode QR berbahaya di Universitas 'Aisyiyah Yogyakarta menggunakan kerangka kerja Lembaga Kehakiman Nasional (NIJ). Enam parameter investigasi didefinisikan: identifikasi domain, identifikasi titik akhir, identifikasi sumber daya pendukung, visualisasi artefak gambar, korelasi stempel waktu, dan rekonstruksi HTML. Data diperoleh dari direktori profil Google Chrome dan dianalisis menggunakan Autopsy, dengan fokus pada artefak Cache Web, Riwayat Browser, dan Cookie. Hasil menunjukkan bahwa lima parameter berhasil diidentifikasi dengan tingkat keberhasilan investigasi sebesar 83,3%, sementara rekonstruksi HTML tidak dapat sepenuhnya dicapai karena keterbatasan cache. Temuan ini menunjukkan bahwa artefak Cache Web memberikan nilai bukti dalam investigasi forensik serangan berbasis Kode QR. Penelitian selanjutnya harus fokus pada peningkatan teknik rekonstruksi halaman penuh. Kata kunci: forensik peramban; artefak digital; NIJ; quishing; web cache